Belajar Matematika Jadi Menyenangkan: Inovasi Pembelajaran dengan Permainan Snake and Ladders di MIS NWDI Selong - Dina Fadillah; Linda Meilya Maulida; Liza Amelia; Ulpah Eka; Neni Agustika; Bq. Yunita Kumalasari; Ardiansyah Ardiansyah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
Service activities in this educational unit are carried out with the aim of fulfilling the teaching assistance program, in which one of the programs is the work program for developing mathematics teaching media in the form of snakes and ladders, the application of the educational game Snakes and Ladders (snakes and ladders) as a mathematics learning innovation in class II MIS NWDI Selong. This game is used as a medium to help students understand the concept of plane shapes and simple addition operations in a fun way. Service activities are carried out through four main stages, namely planning, implementation of learning, and evaluation of activities. The results of the activity show that the application of the Snakes and Ladders game is able to increase students' enthusiasm for learning, strengthen understanding of basic mathematical concepts, and foster teacher enthusiasm in developing creative learning. Educational game media has been proven to be able to create a more active, communicative, fun and meaningful learning atmosphere for elementary school students.